Outdoor thermal comfort research in urban areas of Central and Southeast Europe: A review - Dunjić Jelena (Geographica Pannonica, 2019)
Constant urban population growth and intensive urbanization lead to increased pressure on urban areas leading to uncomfortable living conditions. The quality of urban living conditions often depends on the thermal comfort of the open urban spaces, which are used on the daily basis. That is the reason why the attention towards outdoor thermal comfort (OTC) is increasing in the last decade among the researchers from different fields of expertise. In this article, the review of the outdoor thermal comfort research in urban areas of 11 countries of Central and Southeast Europe in the last decade (2010-2019). The main aim of the review is to give a comprehensive, systematic and complete insight in the current situation in the OTC research interest. The results of the review show increased but uneven interest in outdoor thermal comfort by the end of the research period in countries of the Central and Southeast Europe. In total, 120 articles on the topic of outdoor thermal comfort were identified in the research area. The most significant contribution to the urban outdoor thermal comfort research comes from Hungary, Serbia and Greece. Furthermore, five research objectives were identified: methodology improvement and development, climate sensitive and comfortable urban design and planning, citizens/pedestrian comfort and health assessment and improvement, tourism and health sector support and literature review.